Social isolation and health in widowhood: A qualitative study of Nepali widows' experiences. Issue 12 (1st December 2016) - Houston, Kiely T.; Shrestha, Abina; Kafle, Hari Maya; Singh, Sonal; Mullany, Luke; Thapa, Lily; Surkan, Pamela J.
ABSTRACT: Little research exists on social isolation and health among widows despite their marginalization in South Asia. Using a conceptual framework that delineates distinct forms of social support, our results provide a preliminary analysis of the role social support plays in the well-being of Nepali widows. Between 2011 and 2012, we conducted 42 in-depth interviews in the Kathmandu valley and Surkhet district. Low social support was a common theme, principally lacking in the domains of emotional and instrumental support and was described as increasing women's vulnerability to mistreatment and economic insecurity. Policies and programs that foster these types of support may have positive effects on widows' well-being.